Trade and industrialisation in Africa: SMEs, manufacturing and cluster dynamics - Raphael Kaplinsky; Michael L. Morris (Journal of African Trade, 2019)
Trade in manufacturing through global and regional value chains has played an especially prominent role in global economic growth in recent decades. However, Africa faces severe challenges in growing manufacturing activities in the face of China and Southeast Asia's competitive dominance of global manufactured product markets. Traditionally, global trade is heavily concentrated at the corporate level. But this reliance on large firms as a driver of trade is problematic for Africa given its need for a more inclusive synergistic trade and economic growth path that is more employment intensive, more decentralised and which provides scope for enhanced activities by indigenous and small-scale industry. This is not to argue for the exclusion of large firms or foreign direct investment in economic growth, but rather to argue the case for an increased presence of indigenous small-scale firms in the economy and in export trade. There is evidence of dynamism in Africa, both within individual Small- and Medium-sized Enterprises (SMEs) and in clusters of SMEs. In understanding the challenges faced by this sector, and in examining the prospects for their participation in external trade, we review the experience of 25 African clusters using four dimensions: the nature of unintended externalities (e.g., external economies), market orientation and upgrading and growth trajectories, cluster dynamism and joint action for upgrading, external institutional support and upgrading. In terms of policy challenges for SMEs and export trade we discuss four major areas: (i) participation in governed global value chains feeding into high-income markets, (ii) export sales to non-regional low-income markets, (iii) export sales to regional markets and (iv) informal sector cross-border trade to regional economies. We conclude that for Africa, trade and industrialisation are integrally linked and attempts to facilitate regional trade policies cannot ignore the need for developing appropriate industrial policy and adopting an approach of developmental regionalism. This is especially evident with respect to SME development.
Keywords: 330; African clusters; African trade; global value chains; regional value chains; industrial policy manufacturing SMEs